Never saw me coming : how I outsmarted the FBI and the entire banking system--and pocketed $40 million - Smith, Tanya, 1960- (Little, Brown and Company, 2024)
"In Never Saw Me Coming, Tanya Smith shares her deeply personal and remarkable story of how she went from a precocious young girl to a money-grabbing, computer-savvy wiz. It starts out as a keen interest in technology and innocently acquiring phone numbers to Michael Jackson, as well as other celebrities, and moves to her successfully stealing and depositing $5,000 into her grandmother's banking account. By the time she is 18, the risk taker has confiscated millions in cash. The FBI is hot on her tail and hauls her in for an interview, demanding Smith let them know who she's working for, "as these are not the kind of crimes Black people are smart enough to commit." Their words, indicating that intelligence was determined by race, severely offended Smith. Up for the challenge, she proves the FBI wrong and over time steals $40 million dollars, while securing diamonds, gold bars, and other commodities. Her lifestyle attracts the wrong kind of people, even those who set out to kill her. Law enforcement persisted, ultimately dubbing Smith "one of the single biggest threats to the entire United States banking system." She receives an outrageous prison sentence--the longest for a white-collar offense--and is eventually released by mounting her own brilliant defense."--Amazon.